2018
DOI: 10.1186/s13256-018-1642-y
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya disease in a Moroccan baby: a case report

Abstract: BackgroundA stroke in a baby is uncommon, recent studies suggested that their incidence is rising. Moyamoya disease is one of the leading causes of stroke in babies. This condition is mostly described in Japan. In Morocco, moyamoya disease has rarely been reported and a few cases were published. We report a rare Moroccan case of a 23-month-old baby boy who presented with left-sided hemiparesis and was diagnosed as having moyamoya disease.Case presentationA 23-month-old full-term Moroccan baby boy born to a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…The clinical features of the present case included dysarthria, aphasia, stroke, and hemiparesis on the right side. This is in accordance to the cases reported by Goyal et al, 16 Kim, 13 Okhovat and Moeini, 17 Janda et al, 18 and Houba et al 19 …”
Section: Discussionsupporting
confidence: 93%
“…The clinical features of the present case included dysarthria, aphasia, stroke, and hemiparesis on the right side. This is in accordance to the cases reported by Goyal et al, 16 Kim, 13 Okhovat and Moeini, 17 Janda et al, 18 and Houba et al 19 …”
Section: Discussionsupporting
confidence: 93%
“…It has been seen that seizures and epileptiform electroencephalogram (EEG) changes are common in patients with MMD, as seen in our cases. In children, the re-build-up of slow waves at the end of hyperventilation has been said to be characteristic of MMD [ 2 , 6 ]. Hyperventilation-induced reduction in cerebral blood flow may be responsible for the recurrent TIAs seen in pediatric cases, for example when a child is excited, crying, or forcefully blowing on candles.…”
Section: Discussionmentioning
confidence: 99%
“…The MRA will show classic narrowing of the distal internal carotid artery and/or arteries around the circle of Willis with collaterals. Multiple tiny dot-like flow voids can be noted in the basal ganglia region (due to lenticulostriate and thalamoperforator collaterals) on T2WI and T1WI that enhance on contrast administration [ 6 ]. Bright sulci noted on T2 fluid-attenuated inversion recovery (FLAIR) and post-contrast T1WI form the ‘ivy sign’ due to the engorged pial collateral vessels (with slow blood flow) and thickened arachnoid membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of multiple burr holes through frontal, parietal, and occipital bones has also been shown to provide adequate collateralization with clinical improvement and has been used as primary isolated revascularization, as an add-on to other techniques and as a rescue procedure. [88][89][90][91] This is also one of the least technically demanding revascularization techniques and can be done even under local anesthesia, potentially an attractive option in highsurgical-risk patients. 88 A meta-analysis of 57 publications detailing 1156 pediatric moyamoya disease patients who underwent a total of 1448 revascularization procedures (25% direct, 75% indirect) reported that 87% of those undergoing some form of surgical revascularization had symptomatic improvement.…”
Section: Indirect Revascularizationmentioning
confidence: 99%